Prevalence of polypharmacy in the older adult population within primary care in Portugal: a nationwide cross-sectional study - Simões, Pedro Augusto Gomes Rodrigues Marques (2020)
Introduction Polypharmacy is commonly defined as the simultaneous use of five or more medications; however, there is a lack of consensus regarding the most appropriate definition. It is a significant predictor of morbidity and mortality. The aim of this study was to determine the prevalence of polypharmacy in the population of older adults attending primary care in Portugal and to identify associated sociodemographic and clinical factors. Material and methods We conducted a cross-sectional, analytical study in primary care centres from the five Portuguese healthcare administrative regions and the two autonomous regions. We used a random sample of 757 older adult patients provided by the information department of the ministry of health (SPMS) and family doctors from the autonomous regions. Data collection occurred in March 2018. The variables utilised were sociodemographic characteristics, clinical profile and medication. For each patient, polypharmacy was measured either by the concurrent use of ≥ 5 drugs or by the median number of drugs at the time of data collection. Logistic regression analyses were performed to determine associations between polypharmacy and other variables. Results Polypharmacy (≥ 5 drugs) was present in 77% of the sample. A cut-off of over the median number of drugs was present in 55%. The likelihood of having polypharmacy increased significantly with age (OR = 1.05 (1.02–1.08)), number of chronic health problems (OR = 1.24 (1.07–1.45)) and number of prescribers (OR = 4.71 (3.42–6.48)). Cardiovascular, metabolic and musculoskeletal medications were the most commonly involved in polypharmacy. Conclusions Polypharmacy was a very common occurrence in Portugal. Future primary healthcare policies should address polypharmacy.